Direct comparison of the different conventional laparoscopic positions with the Ethos surgical platform in a laparoscopic pelvic surgery simulation setting - Gözen, Ali Serdar; Rassweiler, Jens (Journal of endourology, 2015)
Objective: Laparoscopic surgery can be harmful to surgeons requiring a prolonged learning curve due to significant ergonomic drawbacks. Based on preliminary clinical experience, we present an experimental evaluation of the second-generation ETHOS™ operating chair by comparing it with two different operating positions of conventional laparoscopic pelvic surgery.Materials and Methods: The ETHOS operation platform consists of a seat like a saddle and five more parts that can be adjusted individually to support the surgeon's trunk and extremities. This operation platform was tested in 30 trainees who performed three standard suturing exercises in a pelvitrainer, approximating a linear and a U-shaped incision, made on the skin of a chicken leg, and completing an urethrovesical anastomosis, on a pig bladder specimen model, using interrupted sutures. The trainees performed each exercise in standing laterally to pelvitrainer (torero position) vs standing behind pelvi-trainer and sitting on ETHOS. The mean values, from all times and for each exercise and position, were documented, and the participants filled out a validated questionnaire focusing on ergonomic issues.Results: There were no significant differences among the different training modalities, in step 1 and step 2. However, in step 3, which mimics the urethrovesical anastomosis, the mean times were statistically significant significantly less by using ETHOS (p<0.0001). The mean times of training in step 3 were 41.2 minutes in the behind the camera position, 49 minutes in torero position, and 39.7 minutes by using ETHOS. The position that was maintained, during the exercises, was mainly responsible for the improvement noted in the ergonomic scores.Conclusions: The new operating platform (ETHOS chair) can significantly improve ergonomics in laparoscopy particularly concerning difficult steps like intracorporeal suturing. This may also improve the urethrovesical anastomosis times in a clinical setting.
Gesehen am 19.11.2018